Predictors of delayed extubation following lung resection: Focusing on preoperative pulmonary function and incentive spirometry. Issue 4 (31st March 2021) - Ko, Hsin-Kuo; Liu, Ching-Yi; Ho, Li-Ing; Chen, Pei-Ku; Shie, Huei-Guan
Abstract : Background: Delayed extubation is one of postoperative pulmonary complications (PPCs). Preoperative pulmonary function test (PFT) is an important assessment for patients undergoing lung resection. Volume-oriented incentive spirometry (IS) is one of physiotherapies to prevent PPCs. Preoperative PFT and IS volume (IS-v) can reflect the physiologic conditions of respiratory system in patients planning to undergo lung resection. However, the relationship between preoperative PFT/IS-v and delayed extubation in patients undergoing lung resection remains unclear. The study investigated the risk factors and impact of delayed extubation after lung resection. We aimed to achieve early recognition of patients being at a higher risk for developing postoperative delayed extubation after lung resection. Methods: This retrospective observational 4-year cohort study was conducted in a medical center, Taiwan. A total of 353 enrolled patients receiving thoracic surgery for lung resection were further categorized into the delayed extubation (n = 142, 40%) and non-delayed extubation (n = 211, 60%) groups. Results: In multivariate logistic regression analyses, age >65 years (adjusted odds ratio [AOR]: 2.60; 95% confidence interval [CI], 1.52-4.45), American Society of Anesthesiologists score >2 (AOR: 1.72; 95% CI, 1.05-2.82), anesthesia time >6hrs (AOR: 1.80; 95% CI, 1.13-2.88), pneumonectomy (AOR: 5.58; 95% CI, 1.62-19.19), and IS-v/inspiratory capacity (IC) ratio (AOR: 2.07; 95% CI, 1.16-3.68) were associated with delayed extubation after lung resection (all p < 0.05). Patients with delayed extubation were significantly associated with a higher proportion of other pulmonary complications, reintubation, mortality, and prolonged intensive care unit and hospital stays. Conclusion: Older age, poor general health status, longer anesthesia time, pneumonectomy, and IS-v/IC ratio could be the independent factors predictive for delayed extubation after lung resection, which was in turn associated with worse outcomes. Preoperative PFT and IS-v were valuable for early recognition of patients being at a higher risk for developing postoperative delayed extubation after lung resection.